Rural Women’s Entrepreneurship and Local Economic Development: A Sustainable Livelihood Framework Perspective - Simbolon, Livia Mariyetta; Simanjuntak, Mariana (Dinasti Publisher, 2026)
This study aims to analyze the effects of livelihood capitals within the Sustainable Livelihood Framework on women’s entrepreneurship and on gender equality in rural communities. The study focuses on four forms of capital, namely human capital, physical capital, social capital, and natural capital, with women’s entrepreneurship treated as a mediating variable and gender equality as the dependent variable. A quantitative research approach was employed using Structural Equation Modeling-Partial Least Square (SEM-PLS). Primary data were obtained through questionnaires distributed to women entrepreneurs in rural areas. The results reveal that human capital and physical capital significantly and positively influence women’s entrepreneurship, whereas social capital and natural capital have no significant effect. These findings suggest that strengthening individual capacities and improving access to productive infrastructure are essential for promoting women’s entrepreneurship in rural areas and advancing gender-inclusive local economic development.